Analisis Stategi Dalam Pengembangan Rencana Kerja Madrasah - Achmad Achmad; Ali Nurhadi; Mahfida Inayati (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
In every educational institution there is a context of quality development through RKS / M (School / Madrasah Work Plan). This is very important in developing a quality institution because this school work plan is the strongest milestone in all aspects of education. Because the work plan of this school and madrasah is a way to develop educational strategies that are used as guidelines by educational institutions. The role of the head of the madrasah in the unit of educational institutions as a manager who is able to design targets and achieve these designs as a milestone in implementing RKM. Strategies, including: Conducting good and effective communication with the madrasah which regarding managerial supervision. With regard to madrasah work plans, arranging workshop schedules for madrasah work plans or being a facilitator in planning and carrying out evaluation, monitoring and also observation in preparation.